Incidence of sight‐threatening diabetic retinopathy in an established urban screening programme: An 11‐year cohort study. Issue 9 (9th June 2021) - Cheyne, Christopher P.; Burgess, Philip I.; Broadbent, Deborah M.; García‐Fiñana, Marta; Stratton, Irene M; Criddle, Ticiana; Wang, Amu; Alshukri, Ayesh; Rahni, Mehrdad M.; Vazquez‐Arango, Pilar; Vora, Jiten P.; Harding, Simon P.; et al.
Abstract: Aims: Systematic annual screening to detect sight‐threatening diabetic retinopathy (STDR) is established in the United Kingdom. We designed an observational cohort study to provide up‐to‐date data for policy makers and clinical researchers on incidence of key screening endpoints in people with diabetes attending one screening programme running for over 30 years. Methods: All people with diabetes aged ≥12 years registered with general practices in the Liverpool health district were offered inclusion. Data sources comprised: primary care (demographics, systemic risk factors), Liverpool Diabetes Eye Screening Programme (retinopathy grading), Hospital Eye Services (slit lamp biomicroscopy assessment of screen positives). Results: 133, 366 screening episodes occurred in 28, 384 people over 11 years. Overall incidences were: screen positive 6.7% (95% CI 6.5–6.8), screen positive for retinopathy 3.1% (3.0–3.1), unassessable images 2.6% (2.5–2.7), other significant eye diseases 1.0% (1.0–1.1). 1.6% (1.6–1.7) had sight‐threatening retinopathy confirmed by slit lamp biomicroscopy. The annual incidence of screen positive and screen positive for retinopathy showed consistent declines from 8.8%–10.6% and 4.4%–4.6% in 2007/09 to 4.4%–6.8% and 2.3%–2.9% in 2013/17, respectively. Rates of STDR (true positive) were consistently below 2% after 2008/09. Screen positive rates were higher in first time attenders (9.9% [9.4–10.2] vs. 6.1% [6.0–6.2]) in part due to ungradeable images (4.1% vs. 2.3%) and other eye disease (2.4% vs. 0.8%). 4.5% (3.9–5.2) of previous non‐attenders had sight‐threatening retinopathy. Compared with people with type 2 diabetes, those with type 1 disease demonstrated higher rates of screen positive (11.9% vs. 6.0%) and STDR (6.4% vs. 1.2%). Overall prevalence of any retinopathy was 27.2% (27.0–27.4). Conclusions: In an established screening programme with a stable population screen, positive rates show a consistent fall over time to a low level. Of those who are screen positive, fewer than 50% are screen positive for diabetic retinopathy. Most are due to sight threatening maculopathy. The annual incidence of STDR is under 2% suggesting future work on redefining screen positive and supporting extended intervals for people at low risk. Higher rates of screen positive and STDR are seen in first time attenders. Those who have never attended for screening should be specifically targeted.